Dimensions of quality of life in Germany: Measured by plain text responses in a representative survey (SOEP) - Gert G. Wagner; Martin Bruemmer; Axel Glemser; Julia Rohrer; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper demonstrates how quality of life can be measured by plain text in a representative survey, the German Socio Economic Panel study (SOEP). Furthermore, the paper shows that problems that are difficult to monitor, especially problems like the state of the European Union, long-term climate change but also the national debt or problems with the quality of consumer goods (like food) and services (like medical treatment), are not issues of particular importance to the majority of people. Developments and risks that are difficult to monitor and only have long-term effects should be left primarily to the discourse conducted by experts and the politically-minded 'elites', the avant garde. And in representative democracies it is ultimately the parliamentarians who must decide. Parliamentarians are likely able to make somewhat better decisions using modern representative surveys and national dialogues than they would be without these instruments of civic participation. Nevertheless, improved civic participation cannot replace parliaments. – – In diesem Beitrag wird gezeigt, dass es heutzutage gut möglich ist, die Wichtigkeitgesellschaftlicher Ziele und dem Stand der Lebensqualität in der Bevölkerung mit Hilfe einesrepräsentativen Surveys (hier: dem Sozio-oekonomischen Panel, SOEP) mit offenen Fragenund Klartextantworten zu erheben und sinnvoll auszuwerten. Dabei zeigt sich, dasslangfristig wichtige, aber zugleich aktuell wenig spürbare Themen wie Klimawandel,Staatsverschuldung oder die Europäische Unionkaum genannt werden. Wir ziehen dieSchlussfolgerung, dass langfristig wirkende Entwicklungen und Gefahren auch weiterhinvorwiegend dem Diskurs der Fachleute und der politisch denkenden 'Avantgarde'zugewiesen werden sollten. Undam Ende müssen in einer repräsentativen Demokratie dieParlamente entscheiden. Auf Basis von modernen repräsentativen Erhebungen undBürgerdialogen können Parlamente vermutlich etwas besser entscheiden als ohne dieseInstrumente der Bürgerbeteiligung. Aber auch eine noch so effektive Bürgerbeteiligung kannParlamente nicht ersetzen.
Keywords: B41; C81; C83; C88; D69; I31; Z13; 330; quality of life; dimensions; open-ended questions; automated text analysis; German Socio Economic Panel study; SOEP